2001
DOI: 10.1086/320746
|View full text |Cite
|
Sign up to set email alerts
|

Venous Access Port–Related Bacteremia in Patients with Acquired Immunodeficiency Syndrome or Cancer: The Reservoir as a Diagnostic and Therapeutic Tool

Abstract: To describe the rate of response to an antibiotic-lock technique (ALT) in the treatment of venous access port (VAP)--related bacteremia and to analyze the role of the reservoir in the persistence of infection, we reported the data from 12 human immunodeficiency virus--infected and 8 oncologic patients with VAP-related bacteremia. The ALT consisted of intracatheter delivery of antibiotics and was associated with a systemic antibiotic infusion. We monitored clinical manifestations and performed qualitative and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 19 publications
2
32
0
4
Order By: Relevance
“…These infections are common, are associated with significant costs, and may be difficult to diagnose in the absence of local signs and symptoms of infection, such as in severely immunocompromised patients [13,14]. Because of the lack of specific diagnostic criteria, clinicians suspecting catheter infection in a patient with a fever of unknown origin and a vascular catheter in place routinely remove the implanted device and initiate broad-spectrum antimicrobial therapy, particularly if the patient is severely neutropenic [1,[4][5][6]. This empirical approach leads to the unwarranted use of antibiotics, thus increasing toxicity, cost and risk of antimicrobial resistance and to the unnecessary removal of the implanted catheters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These infections are common, are associated with significant costs, and may be difficult to diagnose in the absence of local signs and symptoms of infection, such as in severely immunocompromised patients [13,14]. Because of the lack of specific diagnostic criteria, clinicians suspecting catheter infection in a patient with a fever of unknown origin and a vascular catheter in place routinely remove the implanted device and initiate broad-spectrum antimicrobial therapy, particularly if the patient is severely neutropenic [1,[4][5][6]. This empirical approach leads to the unwarranted use of antibiotics, thus increasing toxicity, cost and risk of antimicrobial resistance and to the unnecessary removal of the implanted catheters.…”
Section: Discussionmentioning
confidence: 99%
“…However, diagnosis is very difficult in up to 45% of patients with such infections who do not exhibit these local findings [2], a setting more likely to be observed in immunosuppressed patients, particularly those with profound neutropenia [3]. Because of the lack of specific diagnostic criteria in such patients [4][5][6], many clinicians routinely remove the implanted catheters and initiate broad-spectrum antimicrobial therapy in patients with a vascular catheter and a fever of undetermined origin. This empirical approach results in the unnecessary removal of these devices and the unwarranted use of antibiotics, thus increasing toxicity, cost and risk of antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Although vancomycin and heparin have been frequently used as ALT in the salvage treatment of catheter-related staphylococcal bloodstream infections, several studies have reported the failure of response or salvage of CVCs with this combination (1,13,18,19,21). A combination of minocycline and EDTA (M-EDTA) has been shown to be synergistically active in eradicating microorganisms embedded in biofilm (29).…”
mentioning
confidence: 99%
“…However, the use of an antimicrobial lock in the treatment of CLABSI has not consistently been successful (16,(33)(34)(35)(36). Vancomycin alone or in combination with heparin was associated with a major failure against CLABSI caused by S. aureus (16,34).…”
Section: Discussionmentioning
confidence: 99%